Developing Environmental Care Attitudes and Scientific Literacy through Sasi Local Wisdom-Based E-Modules - Rediani, Ni Nyoman; Kaize, Bernadetha Rizki; Hanifah , Sri; Nainggolan, Herrio Tekdi; Dharma Sanjaya, Pande Made; Hallatu, Trinovianto G.R (Universitas Pendidikan Ganesha, 2023)
The lack of scientific literacy skills and environmental care attitudes possessed by students, which will later impact environmental preservation, is why this research aims to examine the impact of local wisdom-based E-module